1996
DOI: 10.1210/mend.10.12.8961259
|View full text |Cite
|
Sign up to set email alerts
|

Ten years after: reclassification of steroid-responsive genes.

Abstract: Although several hundred genes are directly or indirectly regulated by steroid hormones, significant gaps exist in our understanding of the relevant mechanisms, particularly for those genes that do not directly bind intracellular receptors or that exhibit delayed changes in transcription rates upon receptor binding. To assist in defining the mechanism of action of steroid hormones, we are proposing that a standard nomenclature be adopted for classifying steroid-responsive genes, based upon whether the receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 2 publications
0
28
1
Order By: Relevance
“…Our results do not distinguish a pure secondary response from a recently proposed delayed primary response mechanism [19]. A classic secondary response consists of inducer 1 inducing an independent inducer 2 that is solely responsible for the induction of the measured gene product.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Our results do not distinguish a pure secondary response from a recently proposed delayed primary response mechanism [19]. A classic secondary response consists of inducer 1 inducing an independent inducer 2 that is solely responsible for the induction of the measured gene product.…”
Section: Discussioncontrasting
confidence: 88%
“…It is well known that only a few minutes are required for activated GR to enter the nucleus and bind to a simple promoter regulating gene expression [12,19]. This implies that the regulation of cjun expression by Dex most likely is not by the mechanism of directly and solely binding of GR to the c-jun promoter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng and Pollard (35) showed that uterine expression of c-rasH and ornithine decarboxylase increased 6-12 hr after estradiol treatment. Dean and Sanders (36) suggested that there are two classes of genes which respond to estrogenic stimuli in a delayed manner: the secondary response genes that are dependent on the products of the early primary response genes for their stimulation, and the delayed primary response genes that are dependent on a direct interaction of steroid receptor with the gene's promoter and concomitant enhancement by a product of the early primary response gene. It may be that the delayed response genes stimulated by E2 in both S-D and F344 rats are not induced by BPA in the S-D rat but are induced by BPA in the F344 rat; this possibility requires further investigation.…”
Section: Resultsmentioning
confidence: 99%